The Contemporary Globalized Risk Society and Human Improvement in Transhumanism and Posthumanism (Revista Iberoamericana de Bioética, 2020)
This article seeks to understand contemporary globalized society as a society formed by the validity biotechnoscience, represented in particular by the transhumanism and posthumanism projects. With this objective, the article addresses the question of structural risks and proposes a conceptual analysis and a genealogy of the concepts of “risk”, “danger” and “damages” as well as the contemporary development of transhumanism and posthumanism. It does so from philosophical criticism approach, understood as a therapy for the concepts and arguments we use in attempting to clarify and even dismantle or deconstruct problems when perceived from a less emotionally committed perspective.
Keywords: contemporaneity; globalization; risks; transhumanism; posthumanism